2019
DOI: 10.1002/oa.2770
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater fishing at the Neolithic site of Rakushechny Yar

Abstract: The multilayer settlement site of Rakushechny Yar is located at the northwestern end of an island on the Lower Don River, Rostow region, Russia. It is one of the earliest Neolithic sites in the region, dating from the 7th to the 6th millennia cal BC. During the excavation of the settlement, numerous fish remains were found. To gain an impression of the fish species caught, the largest assemblages, recovered during recent excavations, from the Early Neolithic layers and one pit dated to the middle of the 6th mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Therefore adult anadromous fish, having fed mainly in the marine environment, maintains a relatively enriched δ 13 C signature even when caught up-river (McCarthy and Waldron 2000 ). Sturgeons are the third most represented species in the fishbone assemblage (Zabilska-Kunek 2019 ). Conversely, pots with relatively depleted 13 C are more in keeping with freshwater fish such as cyprinids ( Cyprinidae) and Wels catfish ( Silurus glanis ), constituting the major part of the fish remains in Rakushechny Yar (Zabilska-Kunek 2019 ), or even juvenile sturgeon which would still provide a more freshwater signal (Doucett et al 1999 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore adult anadromous fish, having fed mainly in the marine environment, maintains a relatively enriched δ 13 C signature even when caught up-river (McCarthy and Waldron 2000 ). Sturgeons are the third most represented species in the fishbone assemblage (Zabilska-Kunek 2019 ). Conversely, pots with relatively depleted 13 C are more in keeping with freshwater fish such as cyprinids ( Cyprinidae) and Wels catfish ( Silurus glanis ), constituting the major part of the fish remains in Rakushechny Yar (Zabilska-Kunek 2019 ), or even juvenile sturgeon which would still provide a more freshwater signal (Doucett et al 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the observation of typical morphological traits (Esmaeili et al 2007 ), these are believed to belong to members of the cyprinid family (e.g. common bream, Abramis brama , carp, Cyprinus carpio , asp, Aspius aspius or tench, Tinca tinca ) widely present in the archaeological fish bone assemblage at the site (Zabilska-Kunek 2019 ). In contrast to cyprinids, the other types of fish recovered from the archaeological record at Rakucheshny Yar, such as Wels catfish and sturgeon, have scale-less bodies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of sites are settlements represented by various pits, platforms, artefact scatters and other ephemeral structures, often located close to major rivers or their tributaries 12 . Faunal and botanical analyses have shown that a broad spectrum of hunted, gathered and fished resources was exploited across the study area [13][14][15] .…”
mentioning
confidence: 99%